Disruptions of rpiAB Genes Encoding Ribose-5-Phosphate Isomerases in E. coli Increases Sensitivity of Bacteria to Antibiotics - Tatyana A. Seregina; Rustem S. Shakulov; Svetlana A. Sklyarova; Alexander S. Mironov (Cells)
In Escherichia coli cells, the main enzymes involved in pentose interconversion are ribose-5-phosphate isomerases RpiA and RpiB and ribulose-5-phosphate epimerase Rpe. The inactivation of rpiAB limits ribose-5-phosphate (R5P) synthesis via the oxidative branch of the pentose phosphate pathway (PPP) and unexpectedly results in antibiotic supersensitivity. This type of metabolism is accompanied by significant changes in the level of reducing equivalents of NADPH and glutathione, as well as a sharp drop in the ATP pool. However, this redox and energy imbalance does not lead to the activation of the soxRS oxidative stress defense system but the increased sensitivity to oxidants paraquat and H2O2. The deletion of rpiAB leads to a significant increase in the activity of transketalase (Tkt), a key enzyme of the nonoxidative branch of the PPP and increased sensitivity to ribose added in the growth medium. The phenotype of supersensitivity of rpiAB to antibiotics and ribose can be suppressed by activating the utilization of sedoheptulose-7-phosphate, which originates from R5P, to LPS synthesis or limitation of nucleoside catabolism by the inactivation of the DeoB enzyme, responsible for conversion of ribose-1-phospate to R5P. Our results indicate that the induction of unidirectional synthesis of R5P is the cause of supersensitivity to antibiotics in rpiAB mutant.